Development and evaluation of a quantitative assay detecting cytomegalovirus transcripts for preemptive therapy in allogeneic hematopoietic stem cell transplant recipients. Issue 7 (6th March 2017) - Ishii, Keiko; Onishi, Yasushi; Miyamura, Namiko; Fukuhara, Noriko; Ishizawa, Kenichi; Nakanishi, Mutsumi; Ohnaka, Satoru; Miyasaka, Tomomitsu; Kanno, Emi; Kawakami, Kazuyoshi; Harigae, Hideo; Kaku, Mitsuo
Abstract : Successful preemptive therapy for cytomegalovirus (CMV) infection after hematopoietic stem cell transplantation (HSCT) depends on the availability of a rapid and sensitive assay to guide early treatment. Currently, the antigenemia assay and the quantitative real‐time PCR (qPCR) assay are widely used for this purpose, but they have distinctive concerns. This study aimed to develop and evaluate a novel CMV diagnostic test based on transcription‐reverse transcription concerted reaction (TRC), an RNA‐detecting technology. The CMV‐TRC assay detected CMV β2.7 transcripts within 10 min over a five‐log range. Among a total of 219 samples obtained from 24 allogeneic HSCT recipients, samples detected as positive by the CMV‐TRC assay showed a relatively strong correlation with those detected as positive by the qPCR assay and the antigenemia assay. The CMV‐TRC assay showed higher sensitivity (77.7%) than the antigenemia assay (68.1%) and detected the first and recurrent episodes of active CMV infection in HSCT patients significantly earlier than the antigenemia assay ( P < 0.001). Although the CMV‐TRC assay (87.8%) showed low sensitivity compared to the qPCR assay (96.3%), the performance of the CMV‐TRC assay was equivalent to that of the qPCR assay in detecting the appearance of active CMV infection episodes ( P < 0.092) or rather superior in detecting the clearance of episodes ( P < 0.001). The CMV‐TRC assay with several advantages may be useful for guiding preemptive anti‐CMV therapy in HSCT recipients.